Biosynthesis of cell wall peptidoglycan and polysaccharide antigens by protoplasts of type III group B Streptococcus. - Yeung, M K (1983)
The formation of a nascent peptidoglycan-group-specific antigen of type III group B Streptococcus at the cell membrane level was demonstrated with an M-1 mutanolysin-prepared protoplast system. Protoplasts of group B streptococci in suitably stabilized medium (20% sucrose) readily incorporated [3H]acetate into cell surface macromolecules. Four major polysaccharides were isolated from the protoplast cultural supernatant fluid: the peptidoglycan group-specific antigen polymer, the group B-specific antigen, and the low-molecular-weight and high-molecular-weight forms of the type III polysaccharide antigen. Biosynthesis of all four polymers was not affected by the action of chloramphenicol, indicating protein synthesis was not required for the production of polysaccharide in this system. However, all but the low-molecular-weight type III antigen were inhibited by the action of bacitracin, suggesting that three of the polymers share a common synthesis-assembly site in the membrane. Attachment of the high-molecular-weight antigen to the nascent peptidoglycan-group B antigen complex did not occur in the protoplast system, suggesting that a more complex cell wall matrix may be necessary before linkage of the high-molecular-weight antigen takes place.